Repeated Socialization of Deprived Personality: Macro- and Mіcrоfactors and Sinergetic Approach - Goshovsky, J. O. (Psychological Prospects Journal, 2011)
Speech goes in the article about socially psychological features of resocialisation as repeated socializations of deprived personality. The specific of involving of resocialisation efforts is exposed for the grant of рsychological rehabilitation help of personality, which is in the mode of different deprivation.
Keywords: resocialisation рsychological rehabilitation repeated socialization deprivation deprived personality sinergetic mіcrоfactor macrofactor